2020
DOI: 10.4236/jdm.2020.104019
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Gestational Diabetes: A Systematic Review

Abstract: In March 2020, the World Health Organization declared a pandemic state in response to the number of infected and killed by COVID-19. Gestational diabetes (GD) is characterized by physiological changes making pregnant women even more vulnerable to viral respiratory infections, such as SARS-CoV-2. For these reasons and due to the restriction of data related to DMG and the involvement by COVID-19, the importance of raising information about these two conditions is evident. Therefore, this study aimed to perform a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In 2020, Miola et al (2020) asserted that differences between studies concerning complications pertaining to COVID-19 in women with GDM exist. Findings of four studies relating to pregnant woman with GDM who have had COVID-19 showed that there was limited evidence that COVID-19 exacerbated the problem [ 18 ]. Wei et al, in 2021 in a systematic review and meta-analysis, concluded that severe COVID-19 was vigorously associated with gestational diabetes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Miola et al (2020) asserted that differences between studies concerning complications pertaining to COVID-19 in women with GDM exist. Findings of four studies relating to pregnant woman with GDM who have had COVID-19 showed that there was limited evidence that COVID-19 exacerbated the problem [ 18 ]. Wei et al, in 2021 in a systematic review and meta-analysis, concluded that severe COVID-19 was vigorously associated with gestational diabetes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%